Curvas pontuadas com semigrupo de weierstrass simétrico - Carlos Mejía Alemán (2015)
This work details a part of the article of Contiero and Stöhr [CS], where is approached the estimatives for the dimenson of MS through a construction explicit of its compactification, where the original moduli space is seen as an open on a bigger space, where is allowed that the curves admit singularities, since they are Gorenstein.